3D Metric-aligned and orthogonal solution adaptive mesh generation. (2017) - Marcum, D.; Alauzet, F.
Abstract: A new 3D metric-orthogonal method for metric-based anisotropic tetrahedral mesh generation is presented. The approach uses an advancing-point type point placement that aligns the elements with the underlying metric field and creates quasi-structured local topology. It is based on well-proven methodology and adds novel point-placement strategies that produce solution-adapted anisotropic meshes that are optimal in size and alignment with the solution gradients upon which the metric field is based. The overall methodology is extended to 3D from a previously developed 2D process. Results for several analytical and actual CFD simulation examples are presented that demonstrate that aligned high-quality anisotropic tetrahedral meshes which are optimal for the solution process can be reliably generated.